WORD ORDER AND CONSTITUENCY OF SERIAL VERB CONSTRUCTIONS - Yang, Yongzhong (Lingua Posnaniensis, 2013)
The goal of this paper is to provide a unified account of word order and constituency of serial verb constructions (SVCs) in the framework of generative grammar. It is argued that both SVO-type and SOV-type SVCs follow the Temporal Iconicity, which is associated with the asymmetric nature of syntactic structure, i.e. V1 or VP1 c-commands V2 or VP2 asymmetrically. Based on this argument, an analysis for the derivation of SVCs - Inter-VP Asymmetrical C-command Analysis - is proposed to account for the derivation of SVCs in various languages. It is argued that in the SVC there exists a null predicate and a null argument, the occurrence or non-occurrence of which gives rise to different types of SVCs. Furthermore, left peripheral deletion (LPD) triggers the movement of VP1’s Spec to [Spec IP] and the occurrence of VP2’s Spec as pro, as a result of which VP1 asymmetrically c-commands VP2. Object gapping triggers the ATB movement of VP2 to generate various types of SVCs. The differences between coordinative constructions, pivotal constructions and SVCs lie in their internal structure but not in the verb position.